Early growth performance of Bambara groundnut (Vigna subterranean) landraces in Serdang, Malaysia - Belel, M. D.; Abd Halim, Mohd Ridzwan; Mohd Saud, Halim; Yusop, Mohd Rafii (2014)
A field experiment was carried out to evaluate the growth performance and adaptability of six Bambara groundnut (Vigna subterraneum L.) landraces from Nigeria and one selected variety for Southeast Asia. The Nigerian landraces were Bambwus, IndaraAyaghayagha, Kurvu, Tanyanyi, Karamagdanda and KwadaZwanlang and the selected variety grown in Souheast Asia was Songkla1. The trial was conducted at Universiti Putra Malaysia (UPM) research farm in Serdang, Selangor. Data were collected on growth characters (emergence, plant height, number of leaves, number of petioles, leaf area index, total leaf area and leaf chlorophyll content) during the first 6 weeks of its growth. Results revealed significant variations among the landraces and the selected variety. In general the landraces performed better than the adapted variety (Songkla1) and some of these landraces could be selected for planting in the tropical humid climate of Malaysia.